New species and new records of the predaceous midge genus Parabezzia Malloch (Diptera: Ceratopogonidae) from Brazil - Felippe-Bauer, Maria Luiza; Spinelli, Gustavo R. (Zootaxa, 2015)
Four new species of predaceous midges of the genus Parabezzia Malloch are described and illustrated based on female specimens from southeastern Brazil. Two species are recorded for the first time from Brazil, Parabezzia costalis Wirth from Rio de Janeiro State and P. balseiroi Spinelli & Grogan from Rio Grande do Sul State.